Periodontal Diseases as a Risk Factor for Severe Course and Mortality in COVID-19 – An Interdisciplinary Analysis in Light of Available Studies - Marcjasz, Piotr; Bioły, Anna; Borończyk, Agnieszka; Zając, Piotr; Buliszak, Agnieszka; Babczyńska, Monika (Quality in Sport, 2025)
Introduction: COVID-19 can progress to life-threatening illness in some patients, and identifying modifiable risk factors for severe outcomes is crucial. Periodontal diseases cause systemic inflammation and share risk factors with conditions linked to worse COVID-19 outcomes [7]. Recent studies worldwide have suggested that periodontitis may independently aggravate COVID-19 severity [5]. This interdisciplinary analysis aims to examine current evidence on whether periodontal disease is a risk factor for severe COVID-19 progression and mortality. Materials and methods: A literature review was conducted using the databases such as Pubmed and Google Scholar. Summary of Current Knowledge: An emerging body of global research indicates a significant association between poor periodontal health and adverse COVID-19 outcomes. Multiple studies report that COVID-19 patients with periodontitis experience higher rates of severe complications, including need for intensive care, mechanical ventilation, and death [1, 2]. Conclusion: Current evidence suggests periodontal disease is a plausible and potentially modifiable risk factor for severe COVID-19. Interdisciplinary efforts in dentistry and medicine are warranted to further clarify this relationship and to integrate oral health into risk assessment and management of systemic diseases like COVID-19.